Тараканище: [стихи] / Корней Чуковский - Чуковский Корней Иванович (Читаем с мамой, 2011)
Экземпляры: Ф-3 (20161014) / Инвентарный номер: 50250 / Цена: 40.00 / Сис.шифр: Д / Авт.знак: Ч-88 / ГРНТИ: 17.82.93 / ББК: 84 (2 Рос=Рус)6-44